The level of awareness, knowledge and perception of linked data by library and information science professionals in Nigeria (2023)
The internet is the most compelling capacity building tool, as it exposes various forms of human knowledge. This has resulted into an overwhelming use of the search engines by digital generation in their social, education and research activities. Surprisingly, only a very little fraction of libraries’ digital collections are available on search engine results. Linked Data (LD) is an emerging set of standards and technologies that can potentially enable information systems such as libraries to publish their highly treasured wealth of knowledge, and interlink their hidden data on the web for better global accessibility. Linked Data having been presented as the future for library and information data management has triggered many institutions to experiment with it, and to learn more about the technology. Although technical challenges are paramount obstacles to the spread of LD across libraries, but the biggest issue can be attributed to lack of awareness on its potentials. This research focused on investigating the level of awareness, knowledge and perception of linked data by library and information science (LIS) professionals in Nigeria. The study made use of Survey research design, consisting of structured and open ended questions, distributed to LIS professionals in Nigeria. A total of 71 LIS professionals that spread across 17 institutions in Nigeria formed the participants for the study. The study portrays that LIS professionals in Nigeria perceive LD technology as a welcome innovative idea to facilitate records accessibility, and further move librarianship in Nigeria to the global best practices. But there is a drastic low level of knowledge on the subject of LD amongst the professionals, which is an impediment to the speedy implementation. To this effect, every institution in Nigeria needs to escalate discussions and trainings on the subject of Linked Data in order to foster the development of this powerful tool in shaping libraries collections’ management